Hidrogeomorfologia da Ilha da Trindade: fatores físicos condicionantes da única rede hidrográfica permanente nas ilhas oceânicas brasileiras - Cristiano Pena Magalhães Marques (2017)
Conceptually considered landmasses that are smaller than continents, surrounded by water on all sides and supported by the ocean’s floor, the oceanic islands represent a unique environment on the planet, almost as outdoor labs. In this perspective, the Trindade Island, which is the studied object on the present work, represents the Far East of the Brazilian territory, as well as of the Vitória-Trindade Chain (CVT), that corresponds to a linear sequence of seamounts generally directed to the east-west and located in the South Atlantic Ocean. The geological and climatic nature of the volcanic islands, which have mostly low annual rainfall and high pressure on water resources, do not promote the occurrence of permanent fluvial elements, as the occurrence of superficial perennial drainage is associated to specific climatic, geological and geomorphological factors. However, Trindade has perennial springs and watercourses, which leads to one of the main elements that have driven the accomplishment of this work. Therefore, assuming the hypothesis that the hydrogeomorphological configuration of Trindade is unique in Brazilian territory, the main objective of the research is to characterize and comprehend the hydro geomorphological framework of Trindade’s hydrographic network, identifying the superficial drainage regimes and the types of springs in this territory. The specific goals are: (I) to investigate the role of the surface waters on the geomorphological configuration of the Island, in terms of priority processes of erosion and sedimentation, and its main resulting superficial forms and formations; and (ii) to investigate and comprehend the characteristics of the hydrological subsuperficial component of the drainage of the Island, analyzing the periods of the waters into the subterranean environment and their geomorphological role. In this sense, the results indicated that the Trindade’s river system presents features that are typical from the sediment production zones, or from the called headwaters. In addition, the existence of areas that show different characteristics in relation to the superficial drainage behavior was pointed out, that is, patterns were identified, or types of drainage areas along the Island. From this perspective, 33 hydrographic basins were identified in Trindade, as well as a myriad of small direct drainage areas and 32 springs. In turn, it was found that the waters of the springs of Trindade are not extremely recent waters, and would be the direct result of the rain, which is common on almost daily basis in the Island. In other words, that means that they were possibly kept stored in the island’s aquifer systems and their occurrence are strongly related to the presence of materials that support their infiltration and storage, to the detriment of such rain. Finally, it was pointed out that geochemical loss promoted by Trindade’s springs is quite significant, which confirmed the geomorphological role played by these elements, demonstrating their relevance as important vehicles of geochemical denudation.